The Effect of Qur’an Memorization on Arabic Language Comprehension Ability at Hidayatullah Institute in Batu City - faqih zaenal abidin (Education Research Center, 2025)
This study stemmed from the researcher’s observation of varying levels of Qur’an memorization among students; some exhibited strong memorization abilities, while others showed lower levels. The researcher also noticed a clear gap in Arabic language achievement between students with strong Qur’anic memorization skills and those without. Based on this background, the researcher aimed to examine the relationship between Qur’an memorization and academic performance in Arabic, specifically among second-level female students at Hidayatullah Islamic Institute in Batu City.The research employed a population-based correlational method using regression analysis as the analytical tool. The population consisted of all second-level female students at the institute, totaling 26 students in one class. Data were collected through documentation of Qur’an memorization scores and the results of an achievement test in Arabic.The results of the analysis revealed the following regression equation: Y = 32.117 + 0.628X The hypothesis test showed that the calculated t-value was 4.007, which exceeded the table t-value of 2.604 at a 5% significance level. This indicates that the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. The coefficient of determination (R²) was 40.1%, suggesting that 40.1% of the variance in Arabic language scores can be explained by Qur’an memorization. Based on these findings, the study concludes that Qur’an memorization has a statistically significant impact on students’ academic performance in the Arabic language among second-level female students at Hidayatullah Islamic Institute in Batu City.